The Relationships among Perceived Internal Corporate Social Responsibility, Organizational Trust and Perceived External Prestige - Bista, Sita (International Research Journal of MMC, 2022)
This paper aims to evaluate the relationship among internal corporate social responsibility perception, perceived external organizational prestige and organizational trust. There were 149 respondents from 4 commercial banks of Nepal. The data were collected in 2020 AD, through self-administered questionnaire for each variable. The findings show that internal CSR and trust has positive and significant relationship. However, Internal CSR and perceived external prestige of organization as well as trust and prestige have insignificant relationship.